Association of Pesticides Exposure with Breast Cancer in West Sumatera Province, Indonesia - Yuniar Lestari; Rima Semiarty; Wirsma Arif Harahap (Journal of Midwifery, 2019)
Breast cancer cause multifactorial, one of the risk factors is exposure of pesticides. The aim of this study was to determine association of pesticides exposure with breast cancer in West Sumatera Province, Indonesia. In this cross sectional study, the data were collected from Dr. M Djamil General Hospital Padang. Sampling technique with convenience sampling. We selected 234 patients with breast cancer diagnosed. The variables of this study included independent variable is exposure pesticides and dependent variable is breast cancer. Pesticides exposure were collected from the questionnaire of pesticides exposure that have been validated. The association was analyzed by using chi-square test and cut off point analyzed using receiver operating characteristics (ROC). A two-tailed P-value of <0.05 was considered statistically significant. Data  were  analyzed  using  the SPSS version 22.0. The results of study found that more than half of respondents (53.8%) were exposed of pesticides while less than half of respondents (46.2%) were not exposed. This study confirmed no association of pesticides exposure with breast cancer in West Sumatera Province, Indonesia